Strategi Distribusi Zakat Laznas Yatim Mandiri Melalui Program Pemberdayaan Ekonomi (Studi Pada Lembaga Amil Zakat Nasional Yatim Mandiri Kepanjen) - Rizal; Prayogi R. Saputra; Fiika Tiasari (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2021)
Poverty is a common problem in every country. Meanwhile, zakat is one of the instruments Islamic public finance, one of which is as a medium for distribution of wealth and alleviation poverty. Yatim Mandiri is one of the amil zakat institutions that manages zakat which is has an economic empowerment program through the Bunda Mandiri Sejahtera (BISA) program. Study it focuses on the CAN program. This study uses a qualitative method with a approach descriptive technique where the data found are presented and then analyzed. This research held at LAZNAS Yatim Mandiri. The results of this study indicate that the distribution strategy Zakat Yatim Mandiri uses two methods, namely, the consumptive method, and the productive method. Fund distribution zakat through the Bunda Mandiri Sejahtera economic empowerment program by providing loans Revolving capital has a positive impact on the business development of program participants